Arctic-Mid-Latitude Linkages in a Nonlinear Quasi-Geostrophic Atmospheric Model - Dörthe Handorf; Klaus Dethloff; Sabine Erxleben; Ralf Jaiser; Michael V. Kurgansky (Advances in Meteorology)
A quasi-geostrophic three-level T63 model of the wintertime atmospheric circulation of the Northern Hemisphere has been applied to investigate the impact of Arctic amplification (increase in surface air temperatures and loss of Arctic sea ice during the last 15 years) on the mid-latitude large-scale atmospheric circulation. The model demonstrates a mid-latitude response to an Arctic diabatic heating anomaly. A clear shift towards a negative phase of the Arctic Oscillation (AO−) during low sea-ice-cover conditions occurs, connected with weakening of mid-latitude westerlies over the Atlantic and colder winters over Northern Eurasia. Compared to reanalysis data, there is no clear model response with respect to the Pacific Ocean and North America.